Development of improved technology for the production of strong wines of marsala type on the basis of enzymatic catalysis - Rahimov, Namiq; Kazimova, İlhama; Yusifova, Mehriban; Nasrullayeva, Gunash (Eastern-European Journal of Enterprise Technologies, 2023)
In the assortment of wines produced in the Republic of Azerbaijan, strong wines occupy a significant place. To improve their technology, a number of technological modes and parameters aimed at improving the quality of finished products and the use of modern technology were proposed and tested. As a result of the study, the effectiveness of the use of the mixed-action enzyme preparation Vinozim or Ultrazyme in the production of strong vintage wine of the Marsala type according to the blending scheme using the first must and press fractions was determined. It has been established that the use of this preparation in the process of fermentation of pomace provides a rational supply of phenolic substances for blends of marsala, and in the process of infusion of pomace of nitrogenous components and pentosis. The fundamental possibility of obtaining high-quality wine materials for vintage marsala under the conditions of processing grapes of the variety Bayan-Shirei and Rkasiteli "in the red way" has been studied. Rational modes for obtaining blended wine materials for Marsala, based on the technology of fermentation or long-term infusion of pomace, have been developed. The effect of various enzyme preparations on the quality of wine materials for Marsala has been studied; a rational variant of blending and aging of wine materials for Marsala was experimentally substantiated. It has been established that the rational option for obtaining vintage marsala is a blend of dry-fortified wine material and mistel, or dry-fortified wine material and vacuum must. Analysis of the dynamics of maturation of blended wine materials and data on changes in their chemical composition confirmed the choice of a rational scheme for their production and made it possible to establish the expediency of aging blends for marsala for 2.5 years. To improve the quality of ordinary marsala wine, a new technique for producing vacuum must was devised